The Effect of Training and Competency on Teacher’s Performance - Herlina, Herlina; Arafat, Yasir; Rahman, Andi (Journal of Social Work and Science Education, 2024)
This study aims to ascertain how training and proficiency affect kindergarten/PAUD teachers' performance in Central Bangka Regency. In Central Bangka Regency, 80 instructors were included in the sample size. Purposive sampling was used for the sampling process, and some instructors from Central Bangka Regency served as the respondents. 90 statement items were measured by distributing questionnaires using a 5-point Likert scale to collect the data. Multiple linear regression analysis is the method utilized for analysis. The study's findings demonstrate that teachers' performance is significantly impacted by both competency and training at the same time. Second, the impact of the training on teachers' performance is both partial and considerable. Third, the performance of teachers is partially and significantly impacted by competency.